2021
DOI: 10.1136/bcr-2020-240095
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 myocarditis and postinfection Bell’s palsy

Abstract: Here we present the case of a 37-year-old previously healthy man who developed fever, headache and a unilateral, painful neck swelling while working offshore. He had no known contact with anyone with COVID-19; however, due to the ongoing pandemic, a nasopharyngeal swab was performed, which was positive for the virus. After transfer to hospital for assessment his condition rapidly deteriorated, requiring admission to intensive care for COVID-19 myocarditis. One week after discharge he re-presented with unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…A total of 221 patients with MIS-A were identified: 102 were from the CDC’s MIS-C surveillance system, of whom 55 were described in a recent publication 3 ; 20 were from voluntary reports to the CDC, of whom 9 were included in a recent publication 2 ; and 99 were from case reports published in the literature. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 221 patients with MIS-A were identified: 102 were from the CDC’s MIS-C surveillance system, of whom 55 were described in a recent publication 3 ; 20 were from voluntary reports to the CDC, of whom 9 were included in a recent publication 2 ; and 99 were from case reports published in the literature. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…In total, 449 relevant articles were identified, and 86 were selected for in-depth review; of these, 60 had data for patients with MIS-A. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Figure 1 summarizes...…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Also, Bell's palsy has been reported post-COVID-19 infection like in our patient. 9,10 Bell's palsy is a lower motor neuron (LMN) facial nerve palsy manifesting with weakness on one side of the face, in the absence of other focal neurological deficits. In a recent retrospective study, the incidence of Bell's palsy in patients with COVID-19 was estimated to be 0.08% (approximately 82 per 100,000 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have described cases of patients with COVID-19 and inflammatory cardiomyopathies, mostly myocarditis [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] but also pericarditis [ 38 , 39 , 40 , 41 , 42 , 43 ]. In some cases, the cardiac disease was the first manifestation of the viral infection [ 21 , 29 , 39 ].…”
Section: Inflammatory Cardiomyopathies and Covid-19mentioning
confidence: 99%
“…Studies about COVID-19 reported modifications in gut microbiota composition induced by the viral infection [ 12 , 13 , 14 , 15 ] and in immune system functions [ 16 , 17 , 18 , 19 , 20 ]. In some cases, studies reported cardiac involvement with a cardiac disease (as inflammatory cardiomyopathies, myocarditis, and pericarditis) as a manifestation of COVID-19 infection [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], too. To date, research to better clarify these topics is ongoing.…”
Section: Introduction: Microbiota and The “Heart–gut Axis”mentioning
confidence: 99%